Mifepristone Accelerates HPA Axis Recovery in Secondary Adrenal Insufficiency - Pejman Cohan (Case Reports in Endocrinology)
Context. Transient secondary adrenal insufficiency (SAI) is an expected complication following successful adenomectomy of ACTH-secreting pituitary adenomas or unilateral adrenalectomy for cortisol-secreting adrenal adenomas. To date, no pharmacological therapy has been shown to hasten recovery of the hypothalamic-pituitary-adrenal (HPA) axis in this clinical scenario. Case Description. A 33-year-old woman underwent uncomplicated unilateral adrenalectomy for a 3.7 cm cortisol-secreting adrenal adenoma. Postoperatively, she developed SAI and was placed on hydrocortisone 15 mg/day, given in divided doses. In the ensuing six years, the patient’s HPA axis failed to recover and she remained corticosteroid-dependent. Quarterly biochemical testing (after withholding hydrocortisone for 18 hours) consistently yielded undetectable serum cortisol and subnormal plasma ACTH levels. While she was on hydrocortisone 15 mg/day, mifepristone was initiated and gradually titrated to a maintenance dose of 600 mg/day after 5 months. Rapid recovery of the HPA axis was subsequently noted with ACTH rising into the supranormal range at 4 months followed by a subsequent rise in cortisol levels into the normal range. After 6 months, the dose of hydrocortisone and mifepristone was lowered and both were ultimately stopped after 8 months. The HPA axis remains normal after an additional 16 months of follow-up. Conclusion. Mifepristone successfully restored the HPA axis in a woman with prolonged secondary adrenal insufficiency (SAI) after adrenalectomy for Cushing’s syndrome (CS).